Metal-free isoamyl nitrite mediated efficient synthesis of 1,2,4-oxadiazoles - Galave, Sharad A.; Kadam, Kishorkumar S.; Sonawane, Amol D.; Pansare, Vaibhav R.; Garud, Dinesh R. (Tetrahedron Letters, 2023)
We report herein, a metal-free isoamyl nitrite mediated efficient synthesis of 1,2,4-oxadiazoles by one pot cycloaddition reaction of aldoximes with nitriles. The structure of the 1,2,4-oxadiazole derivatives was confirmed by studies of spectral analysis. Current methodology provides a novel pathway to access 1,2,4-oxadiazole derivatives.& COPY; 2023 Elsevier Ltd. All rights reserved.
Keywords: 1; 2; 4-Oxadiazole; Aldoxime; Cycloaddition; Isoamyl nitrite